THE ORIGIN AND MEANING OF ENGLISH ANIMALISTIC IDIOMS - POLUZHYN Іvan (Науковий вісник Ужгородського університету. Серія Філологія, 2020)
The article deals with the origin and meaning of English animalistic idioms. The author proposes the definition to the concept of idiom as a sequence of words with special integral meaning that differs from the sense of its constituents. This meaning cannot be deduced from the semantic components of words, constituting the idiom. A number of varieties of idiomatic phrases are given in the article. A contextological approach to the definition of their meaning is substantiated. The topicality of the study theme. As animalistic idioms were not the subject-matter of a separaate investigation, that is so far one does not know which concrete names of living creatures actively participate in forming idioms, the contents of the article are concentrated on filling this gap. The empirical material under study. For obtaining as precise data as possible 100 most frequently used idioms, en- closing a great number of living creature names regardless of their space displacement, have been analyzed. Each of the idioms under consideration is accompanied with a definition and short excursus into the history of its origin. The aim of writing the article is obtaining and making more precise semantic information about each of the animalistic idioms that make up dictionary entries. The following modern methods of linguistic investigation have been applied: phraseological identification, the descrip- tion and analysis of dictionary definitions with selective references to lexicographic and literary sources, which give meaning variants of some animalistic idioms. The results of the given study convincingly prove the availability of keen interest, exhibited by the English ethnos, to the upper appearance, way of life and typical behavior of living creatures, the names of which entailed the formation of animalistic idioms. Categorization of the idioms under investigation has also been proposed that is based on the ability of a certain name of a living creature to form one or more animalistic idioms, that is, to reveal its phraseological potence. The subject-matter of further study may be a comparative aspect of animalistic idiomaticity in closely and distantly related languages.